Recent Lateral Expansion of Sphagnum Bogs Over Central Fen Areas of Boreal Aapa Mire Complexes - Granlund, Lars; Vesakoski, Ville; Sallinen, Antti; Kolari, Tiina H. M.; Wolff, Franziska; Tahvanainen, Teemu (Ecosystems, 2022)
We investigated recent changes in spatial patterning of fen and bog zones in five boreal aapa mire complexes (mixed peatlands with patterned fen and bog parts) in a multiproxy study. Comparison of old (1940–1970s) and new aerial images revealed decrease of flarks (wet hollows) in patterned fens by 33–63% in middle boreal and 16–42% in northern boreal sites, as lawns of bog Sphagnum mosses expanded over fens. Peat core transects across transformed areas were used to verify the remote sensing inference with stratigraphic analyses of macrofossils, hyperspectral imaging, and age-depth profiles derived from 14 C AMS dating and pine pollen density. The transect data revealed that the changes observed by remote sensing during past decades originated already from the end of the Little Ice Age (LIA) between 1700–1850 CE in bog zones and later in the flarks of fen zones. The average lateral expansion rate of bogs over fen zones was 0.77 m y −1 (range 0.19–1.66) as estimated by remote sensing, and 0.71 m y −1 (range 0.13–1.76) based on peat transects. The contemporary plant communities conformed to the macrofossil communities, and distinct vegetation zones were recognized as representing recently changed areas. The fen-bog transition increased the apparent carbon accumulation, but it can potentially threaten fen species and habitats. These observations indicate that rapid lateral bog expansion over aapa mires may be in progress, but more research is needed to reveal if ongoing fen-bog transitions are a commonplace phenomenon in northern mires.